Implementasi Internet of Things pada Sistem Cathodic Protection sebagai Proteksi Korosi Besi Beton - Billy Christian Johan; Agustinus Noertjahyana; Gunawan Budi Wijaya; Daniel Tjandra; Resmana Lim (Jurnal Infra, 2022)
Concrete iron or reinforcement bar is steel used for reinforcement in concrete construction or known as reinforced concrete. Reinforcing bar can undergo a corrosion process caused by chemical or electrochemical reactions between steel reinforcement and its environment. One of many way to protect concrete from corrosion is by cathodic protection. There are two types of cathodic protection, namely sacrificial anodes and impressed current cathodic protection (ICCP). ICCP is more commonly used for protection in reinforced bar structures. In ICCP, negative current flows to the reinforcing bar and positive current flows to the anode. This is a method to protect the reinforcing bar from corrosion. In addition to the corrosion protection system, there is also a half-cell potential test to measure the chance of corrosion of the reinforcing bar. Measurements are made by reading the potential difference between the reference electrode and the reinforcing bar. Chances of corrosion can be known level of corrosion by reading the table of corrosion opportunities with ASTM C879-09 standard.In this research, the implementation of the internet of things will be carried out on the cathodic protection system to protect the reinforcing bar from corrosion, so that the user can monitor and control the provision of cathodic protection on the reinforcing bar.Based on the results of the tests that have been carried out, the IoT system can regulate the power supply by setting the voltage and current and can schedule the power supply to provide electric current to the reinforcing bar and can provide notifications if the electric current flowing in the concrete is more than or less than ICCP standard. The average difference between the readings between the voltage sensor and the multimeter is 21.07 mV. The reading value of the potential difference between the concrete iron and the reference electrode in the half-cell potential test method before it was carried out was -216.15 mV and after ICCP was carried out, the value became -167.974 mV. There was an increase of 58.596 mV after ICCP was performed.